Research of urban agglomerations in the aspect of implementation of the administrative and territorial reform in Ukraine (case study of Kharkiv region) - Kostiantyn Niemets; Kateryna Sehida; Liudmyla Niemets; Kateryna Kravchenko; Yevheniia Telebienieva; Liudmyla Kliuchko; Volodymyr Redin (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2019)
In the modern context of, one of the main tasks in the regional development management is to optimally realize the complex potential of the territories, which requires a comprehensive study of the spatial structure and evolutionary potential of agglomerations of all levels in order to identify disparities in their development, correct imbalances and optimize the spatial organization of the region. The first step to solve this problem is to identify the spatial structure and evaluate the interconnections of agglomerations sequentially, from local to regional level. This is becoming more relevant in the context of administrative and territorial reform in Ukraine. The purpose of this study is to analyze the prospects for the development of urban agglomerations and the organization of the administrative and territorial structure of Kharkiv region in view of the prevailing influence of the city of Kharkiv and the Kharkiv agglomeration. The basic theoretical and methodological starting points of the study of urban agglomerations are presented; their characteristics and parameters of boundary determination were defined. The essence of the method of modeling of integral influence function (IIF modeling) was revealed, the author's research methodology was substantiated. The tendencies of introduction of administrative and territorial reform in Ukraine were analyzed. It was established that Kharkiv region occupies mediocre places in terms of formation of the united territorial communities, there were 23 ones in the oblast (3 of them are city, 12 town, 8 rural ones) by the end of 2019. The scheme for dividing into enlarged districts has not yet been approved. According to different plans / proposals, the existing 27 districts of the oblast should be consolidated into nine, seven, six or four enlarged districts (counties). All of the above proposals were considered by the authors, it is established that the existing projects do not fully cover the main prevailing factors of allocation of competitive districts, do not take into account the role of historically formed system of settlement, spatial-statistical parameters, integral potential of territories, urbanization and agglomeration. The authors performed the IIF modeling and constructed the IIF surface of the weighted average settlement potential of Kharkiv region by the base radius of influence (2, 10, 20, and 30 km), which allowed to determine the features of the Kharkov agglomeration structure and the interaction of the settlements in the region by different radiuses of interaction, primary agglomerations, prospective growth points. On the basis of the obtained results of IIF modeling, the author's model of administrative and territorial division of Kharkiv region into eight enlarged districts was proposed, given the specific features of the settlement system and the correlation of area and population of the modeled administrative and territorial units. The scientifically grounded division of the region into enlarged districts (counties) and stimulation of their development will contribute to the most complete and rational use of the territories potential, increase of economic, human, investment potential, rise of the level and quality of life of the population, etc.